ANÁLISIS DE UN CONFLICTO SOCIOAMBIENTAL POR AGUA Y TURISMO EN SARDINAL, COSTA RICA - Navas, Grettel; Cuvi, Nicolás (Universidad de Costa Rica, 2016)
In this article is analyzed the conflict aroused by the appropriation of water from theaquifer Sardinal in Guanacaste, Costa Rica, between 2008 and 2010. The conflict includeddemonstrations, scientific controversies and trials involving community residents,government representatives, nongovernmental and ecclesiastical organizations, andprivate enterprise. While the conflict was resolved in favor of the community, it did notinvolve a solution of its structural causes: inconsistent actions from state institutions, lackof land use planning, and spatial and economic exclusion of community members fromtourism development.